Safety assessment of the process Greiner Packaging, based on Starlinger deCON technology, used to recycle post‐consumer PET into food contact materials. (20th June 2022) - ,; Lambré, Claude; Barat Baviera, José Manuel; Bolognesi, Claudia; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Mengelers, Marcel; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Greiner Packaging (EU register number RECYC243), which uses the Starlinger deCON technology. The input material is hot washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, e.g. bottles, including no more than 5% PET from non‐food consumer applications. The flakes are preheated before being submitted to solid‐state polycondensation (SSP) in a ■■■■■ reactor at high temperature under vacuum and ■■■■■ Having examined the challenge test provided, the Panel concluded that the preheating (step 2) and the decontamination in the SSP reactor (step 3) are critical in determining the decontamination efficiency of the process. The operating parameters to control the performance of these critical steps are temperature, pressure, residence time and ■■■■■ It was demonstrated that this recycling process is able to ensure a level of migration of potential unknown contaminants into food below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not considered to be of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature, with or without hotfill. The final articles made of this recycled PET are not intended to be used in microwave or conventional ovens and such uses are not covered by this evaluation.